Paradixical Word Collocations in the Structure of Idioms - Mirgalimova, Liliia M.; Ayupova, Roza A.; Arsenteva, Elena F.; Pamies-Bertrán, Antonio (Journal of History Culture and Art Research, 2018)
The paper describes the results of the study of phraseological units with paradoxical word combinations consisting of lexemes that semantically cannot collocate with each other. The empirical material of the research includes units of two widely spoken European languages: English and Russian which were collected from different unilingual and bilingual phraseological dictionaries by using continuous sampling method. The paper begins with a brief review of contemporary research for analyzing paradox as a phenomenon observed in phraseology and studies that might unfold the secrets of using semantically not collocable words as component parts of prototypes of such phraseological units. Etymological data gathered from various sources of the languages analyzed applying the method suggested by E. Piirainen and D. Dobrovol’skij witness to the time the phraseological units were coined the word combinations we are analyzing did not use to sound paradoxical. It is due to some formal or semantic alterations that the prototypical word combinations or their component parts had to undergo they started to sound paradoxical.